2014
DOI: 10.1007/s12640-014-9478-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repetitive Exposure to Anesthetics and Analgesics in the Tg2576 Mouse Alzheimer’s Model

Abstract: The use of anesthetics and sedatives has been suggested to be a contributor to Alzheimer's disease neuropathogenesis. We wanted to address the in vivo relevance of those substances in the Tg2576 Alzheimer's mouse model. Tg7526 mice were anesthesia-sedated for 90 min once a week for 4 weeks. Y maze, Congo Red, and amyloid beta (Aβ) immunochemistry were performed. We did not find any significant change in the navigation behavior of the exposed mice compared to the controls. Significantly less deposition of Aβ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Several animal studies have suggested that BZDs reduce Aβ levels, although the exact mechanism by which this occurs is currently unknown. Repetitive diazepam use significantly reduced Aβ levels in the cortex and hippocampus in an AD mouse model (17); furthermore, a recent invitro study showed that midazolam prevented Aβ formation (18). Another animal study showed that diazepam lowered the levels of Aβ deposition, but exacerbated impaired memory in transgenic mice (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several animal studies have suggested that BZDs reduce Aβ levels, although the exact mechanism by which this occurs is currently unknown. Repetitive diazepam use significantly reduced Aβ levels in the cortex and hippocampus in an AD mouse model (17); furthermore, a recent invitro study showed that midazolam prevented Aβ formation (18). Another animal study showed that diazepam lowered the levels of Aβ deposition, but exacerbated impaired memory in transgenic mice (16).…”
Section: Discussionmentioning
confidence: 99%
“…GABA-A receptor agonists, including certain types of BZDs, may have neuroprotective effects via the attenuation of glutamate-mediated neuronal excitability and beta-amyloid (Aβ) neurotoxicity (11,14,15). Furthermore, several animal studies showed that BZD administration reduced cortical Aβ plaques deposition in mouse brains (16,17). A recent study also highlighted that midazolam, a benzodiazepine, suppressed Aβ formation, suggesting its protective effect against Aβ aggregation (18).…”
Section: Introductionmentioning
confidence: 99%
“…[68] Reduced epileptiform discharges [68] No effect on spike-wave discharges [73] Increased electrographic spike frequency by > 183% of baseline [23] [73]-single dose of 20 mg/kg, i. APP Tg2576 [132] Improved memory [131] Prevented Aβ oligomer accumulation and synapse loss [131] Reduced Aβ deposits in CA1, frontal cortex, and entorhinal cortex [132] [131]-2 μg p.o. 5x/week for 2 months [132]-4 mg/kg/week for 4 weeks [133] Prevented executive dysfunction and longterm memory impairment [133] Enhanced learning and memory [133] Prevented impairment in synaptic plasticity [134] Prevented neuronal loss [134] Inhibited the generation of Aβ leading to reduction in density of amyloid plaques [134] Suppressed activation of microglia and astrocytes [134] Reduced epileptic spikes in the cortex and hippocampus [134] Enhanced levels of BDNF and NGF in the brain [134] Not able to rescue short-term memory deterioration [133] [133]-30 mg/kg/day p.o.…”
Section: Levetiracetam (Lev)mentioning
confidence: 99%
“…It is noteworthy that two hallmark lesions of Alzheimer disease, excessive plaque formation and tauopathy, have been shown to be influenced by general anesthetics (49,50) thus suggesting possible interaction between anesthesia and Alzheimer pathogenesis which may underlie post-operative cognitive decline. The evidence regarding the role of anesthesia-induced calcium imbalance and modulation of inflammatory pathways in the development of POCD is actively being investigated.…”
Section: General Anesthesia and The Aging Brainmentioning
confidence: 99%